1998
DOI: 10.1136/bjo.82.4.346
|View full text |Cite
|
Sign up to set email alerts
|

Fundus autofluorescence in patients with macular holes imaged with a laser scanning ophthalmoscope

Abstract: Aim-To demonstrate the usefulness of a recently developed technique of imaging fundus autofluorescence and to compare it with the results of fluorescein angiography in the diagnosis and staging of macular holes. Methods-The intensity and distribution of fundus autofluorescence was studied in 51 patients with idiopathic macular holes and pseudoholes using a confocal laser scanning ophthalmoscope (cLSO) and the images were compared with those obtained by fundus fluorescein angiography. (Br J Ophthalmol 1998;82:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
163
0
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(175 citation statements)
references
References 18 publications
7
163
0
5
Order By: Relevance
“…Morgan and colleagues later demonstrated that these methods could be used to achieve single cell resolution of the RPE in the living human eye [17]. Since the RPE is important for maintaining the healthy function of the photoreceptor layer and is implicated in many retinal diseases, such as AMD [7][8][9][10][11], the demonstration that these cells were now accessible to optical imaging in the living human eye was a potentially valuable advance. However, our early attempts to image the RPE in patients with AMD using these methods proved difficult; we were able to obtain images with greater structural detail than commercial systems, but individual cells could not be resolved [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morgan and colleagues later demonstrated that these methods could be used to achieve single cell resolution of the RPE in the living human eye [17]. Since the RPE is important for maintaining the healthy function of the photoreceptor layer and is implicated in many retinal diseases, such as AMD [7][8][9][10][11], the demonstration that these cells were now accessible to optical imaging in the living human eye was a potentially valuable advance. However, our early attempts to image the RPE in patients with AMD using these methods proved difficult; we were able to obtain images with greater structural detail than commercial systems, but individual cells could not be resolved [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…These changes may precede and/or accompany RPE cell death and the degeneration of overlying photoreceptors [4,6]. Clinical imaging methods, such as confocal scanning laser ophthalmoscopy (cSLO), are used to examine the FAF pattern as a means of assessing the health of the RPE in AMD and other retinal diseases [7][8][9][10][11]. However, currently available commercial fundus autofluorescence (FAF) imaging systems lack the resolution to identify individual cells, preventing morphometric analysis of the RPE cell mosaic.…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo autofluorescence of human retinal pigmented epithelium (RPE) provides a noninvasive technique that can be used in the investigation of inherited and age-related retinal diseases (36,37), permitting the assessment of the viability of the RPE/photoreceptor complex by the distribution of the levels of retinal fluorophores (38). The ocular fundi of individuals with degenerative macular diseases such as age-related macular degeneration show a dramatic, agedependent accumulation of retinal fluorophores (38).…”
Section: Discussionmentioning
confidence: 99%
“…There is a fine ring of hypoAF just surrounding the hole due to the upturned edges of the macular hole which constitutes of tissue containing luteal pigments and also because the increased thickness there impedes the passage of the excitation rays. 18 Following a successful macular hole surgery, the FAF returns to a normal pattern. (Figure 7) …”
Section: Macular Holementioning
confidence: 99%